2010
DOI: 10.1128/jvi.00704-10
|View full text |Cite
|
Sign up to set email alerts
|

Congregation of Orthopoxvirus Virions in Cytoplasmic A-Type Inclusions Is Mediated by Interactions of a Bridging Protein (A26p) with a Matrix Protein (ATIp) and a Virion Membrane-Associated Protein (A27p)

Abstract: Some orthopoxviruses, e.g., the cowpox, ectromelia, and raccoonpox viruses, form large, discrete cytoplasmic inclusions within which mature virions (MVs) are embedded by a process called occlusion. These inclusions, which may protect occluded MVs in the environment, are composed of aggregates of the A-type inclusion protein (ATIp), which is truncated in orthopoxviruses such as vaccinia virus (VACV) and variola virus that fail to form inclusions. In addition to an intact ATIp, occlusion requires the A26 protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
36
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 25 publications
2
36
0
Order By: Relevance
“…As much more is known about the molecular biology of VACV than about that of CPXV or other OPXVs that make ATIs naturally, we primarily used the reconstructed VACV system to study ATI forma-tion and the mechanism of occlusion. We previously demonstrated that the direct association of A26 with both the A27-A17 complex and the ATIp is required to mediate occlusion (14). In the present study, we showed that ATI enlargement was dependent on both continued protein synthesis and coalescence of smaller ATIs, which was documented by live imaging and confirmed with CPXV.…”
supporting
confidence: 68%
See 3 more Smart Citations
“…As much more is known about the molecular biology of VACV than about that of CPXV or other OPXVs that make ATIs naturally, we primarily used the reconstructed VACV system to study ATI forma-tion and the mechanism of occlusion. We previously demonstrated that the direct association of A26 with both the A27-A17 complex and the ATIp is required to mediate occlusion (14). In the present study, we showed that ATI enlargement was dependent on both continued protein synthesis and coalescence of smaller ATIs, which was documented by live imaging and confirmed with CPXV.…”
supporting
confidence: 68%
“…We demonstrated previously that VACV could be enabled to make ATIs and occlude MVs if the CPXV ATI gene were substituted for the shorter VACV A25 homolog (14). Thus, VACV encodes all of the necessary proteins for this process except for the full-length ATIp.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The ATI matrix is formed by multiple copies of the A25L polypeptide, which corresponds to the CPXV158 protein (30). A26L, also named p4c or CPXV159 protein, is required to direct intracellular mature virions (IMVs) into ATIs (33); the protein has a bridging function between the A25L matrix protein and IMVs containing the membrane-associated A27L (CPXV162 protein) (34). In addition, the capability to embed mature virions in the ATIs was recently shown to influence the virulence of CPXV (35).…”
Section: Isolation Of a Cpxv From A Common Volementioning
confidence: 99%